The Influence of Promotion Strategy, Service Quality and Brand Image on Client Loyalty at PT Semangart Giri Putra - Jenike Bangu Nggona; Zandra Dwanita Widodo; Sri Wijiastuti (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to analyze the effect of Promotion Strategy, Service Quality, and Brand Image on Client Loyalty at PT Semangart Giri Putra, a company engaged in construction services and project procurement. This research is motivated by the company’s need to maintain long-term client relationships amid increasing competition in the construction industry. The variables examined in this study consist of Promotion Strategy (X1), Service Quality (X2), and Brand Image (X3) as independent variables, and Client Loyalty (Y) as the dependent variable. The research employs a quantitative approach using a survey method. The sampling technique used was purposive sampling, with respondents consisting of clients who had previously collaborated with PT Semangart Giri Putra. Data were collected through questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that Promotion Strategy, Service Quality, and Brand Image have a positive and significant effect on Client Loyalty. In addition, Brand Image plays an important role in strengthening the relationship between service performance and client loyalty.